Dispositional Optimism and All-Cause Mortality in Older Adults: A Cohort Study. Issue 8 (26th October 2021) - Craig, Heather Jayne; Ryan, Joanne; Freak-Poli, Rosanne; Owen, Alice; McNeil, John; Woods, Robyn; Ward, Stephanie; Britt, Carlene; Gasevic, Danijela
Abstract : Supplemental digital content is available in the text. ABSTRACT: Objective: Optimism is modifiable and may be associated with healthy aging. We aim to investigate whether dispositional optimism is associated with all-cause mortality in adults 70 years and older. Methods: Between 2010 and 2014, older adults free of serious cardiovascular disease and dementia were recruited through primary care physicians and enrolled in the Asp irin R educing E vents in the E lderly (ASPREE) clinical trial. Australian ASPREE participants were invited to participate in the ASPREE Longitudinal Study of Older Persons (ALSOP) that was running in parallel to ASPREE. Optimism was assessed at baseline using the Life Orientation Test—Revised. The association between optimism, divided into quartiles, and all-cause mortality was assessed using Cox proportional hazards models. Results: A total of 11, 701 participants (mean [standard deviation] age = 75.1 [4.24] years; 46.6% men) returned the ALSOP Social questionnaire and completed the Life Orientation Test—Revised. During a median follow-up of 4.7 years, 469 deaths occurred. The fully adjusted model was not significant (hazard ratio = 0.78, 95% confidence interval = 0.58–1.06). There was evidence that age was an effect modifier of the association between optimism and longevity. Higher optimism was associated with lower mortality risk in the oldest individuals only (77+ years; hazard ratio = 0.61, 95% confidence interval = 0.39–0.96). Conclusions: We observed no independent relationship between optimism and all-cause mortality in the total sample, although optimism seemed to be associated with lower risk among the oldest old (adults 77 years and older).